Damascus Gate - Stone, Robert, 1937-2015. (New York : Scribner Paperback Fiction, 1952)
Christopher Lucas, unsure of his own beliefs, is wandering through Jerusalem, working on an article about religious mania. When he meets Sonia Barnes, dusky nightclub singer, devoted Sufi and mystic, he is entranced. As Sonia helps Lucas meet some of the visionaries and gurus who fill the city, the two suddenly find that they have become pawns in a fanatical bombing plot. Its target is no less than the Temple Mount, the city's holiest site.
Keywords: Jerusalem -- Fiction; Terrorism -- Fiction; Journalists -- Fiction; Adventure fiction; Political fiction